Full-length transcriptome and metabolite analysis reveal reticuline epimerase-independent pathways for benzylisoquinoline alkaloids biosynthesis in Sinomenium acutum - Yang, Yufan; Sun, Ying; Wang, Zhaoxin; Yin, Maojing; Sun, Runze; Xue, Lu; Huang, Xueshuang; Wang, Chunhua; Yan, Xiaohui (Frontiers in Plant Science, 2022)
Benzylisoquinoline alkaloids (BIAs) are a large family of plant natural products with important pharmaceutical applications. Sinomenium acutum is a medicinal plant from the Menispermaceae family and has been used for the treatment of rheumatoid arthritis for hundreds of years. S. acutum contains more than 50 BIAs and sinomenine is a representative BIA from this plant. Sinomenine was found to have preventive and curative effects on opioid dependence. Despite the wide applications of S. acutum, investigation on the biosynthetic pathways of BIAs from S. acutum is limited. In this study, we performed a comprehensive analysis of the transcriptome data and BIAs in the root, stem, leaf, and seed of S. acutum. Metabolic analysis showed an obvious difference in BIA contents in different tissues. Based on the analysis of the full-length transcriptome, differentially expressed genes, and weighted gene co-expression network, we proposed the biosynthetic pathways for a few BIAs from S. acutum, such as sinomenine, magnoflorine, and tetrahydropalmatine, and screened candidate genes involved in these biosynthesis processes. Notably, the reticuline epimerase (REPI/STORR), which converts (S)-reticuline to (R)-reticuline and plays an essential role in morphine and codeine biosynthesis, was not found in the transcriptome data of S. acutum. Our results shed light on the biogenesis of the BIAs in S. acutum and may pave the way for the future development of this important medicinal plant.